Ameboma Mimicking Submucosal Tumor of the Colon in an Elderly - Shen-Yung Wang; Shou-Chuan Shih; Tsang-En Wang; Wen-Hsiung Chang; Horng-Yuan Wang; Shee-Chan Lin (International Journal of Gerontology, 2011)
Ameboma is a rare presentation of intestinal amebiasis, which is caused by infection with Entamoeba histolytica. Amebomas are generally concentric and can be difficult to differentiate from carcinoma in the gastrointestinal tract, which are commonly seen in elderly patients. Radiological studies or colonoscopy can be difficult to provide the diagnosis. We present an elderly man with an ameboma in the ascending colon, which manifested as a submucosal tumor in the radiological or endoscopic studies. His serum antiamebic serology test was positive. He received surgery because of poor response to medical treatment. A full course of antiamebic therapy followed by a luminal agent were given and he had a smooth postoperative course without relapse of amebic infection. Although the elderly population has a higher incidence of colonic malignancy, ameboma should be considered in the differential diagnosis of submucosal tumors in the colon, especially in patients with an insidious onset of disease.